KINERJA PEMERINTAH DAERAH TERHADAP PELAKSANAAN PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM POS PELAYANAN TEKNOLOGI TEPAT GUNA DI KABUPATEN PULANG PISAU : (Studi di Dinas Pemberdayaan Masyarakat Desa Kab Pulang Pisau) - Charles Hutapea (Journal SOSIOLOGI, 2022)
Empowerment is an attempt to change social and economic conditions, based on a plan (plan) towards a better direction, in order to improve the assets and capabilities of the poor. Community empowerment activities can be organized in the setting of geographical areas, sectors, modernity, class, and status. In other words, empowerment is enabling and empowering the community.   This study aims to describe and analyze the performance of the Regional Government in this case the Village Community Empowerment Office in conducting community empowerment through appropriate  technology programs and see the inhibiting and supporting factors of the performance of  the Regional Government in Pulang Pisau Regency.  The research method uses descriptive qualitative research. Data analysis techniques used in this study are through data collection, data reduction, data presentation and verification. This research uses performance measurement theory with Whittaker theory. The indicators include Productivity Indicators, Efficiency Indicators, and Effectiveness Indicators, which are carried out by observation, interviews, and documentation.   The results of this research are input from empowered communities themselves and information that support the implementation of empowerment itself, then in the process are activities that occur or are carried out during the implementation such as training socialization held in each sub-district followed by participating communities earlier in improving the ability and knowledge.